Teacher perception regarding remote pedagogical work during the pandemic COVID-19: El caso del distrito de Nuevo Chimbote -Perú- - Castillo Ramos, Norma Edith; Alegre Jara, Maribel Enaida (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
One of the measures of the Ministry of Education of Peru in the face of the global health emergency COVID 19; was to immediately decree the continuity of the service in the distance education modality; generating a crisis of the process of adaptation and transition to a new way of teaching. The objective was: To determine the level of perception of basic education teachers, regarding their pedagogical work in this modality. Obtaining, among other results, a regular perception (56.8%) in the dimension: necessary skills for the management of virtual tools essential to perform in this new modality.